Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12967-017-1164-1
|View full text |Cite
|
Sign up to set email alerts
|

Veliparib in combination with radiotherapy for the treatment of MGMT unmethylated glioblastoma

Abstract: BackgroundThe O 6-methylguanine methyltransferase (MGMT) gene is frequently unmethylated in patients with glioblastoma (GBM), rendering them non-responsive to the standard treatment regime of surgery followed by concurrent radiotherapy (RT) and temozolomide. Here, we investigate the efficacy of adding a PARP inhibitor, veliparib, to radiotherapy to treat MGMT unmethylated GBM.MethodsThe inhibition of PARP with veliparib (ABT-888), a potent and orally bioavailable inhibitor in combination with RT was tested on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Thanks to inhibition of BER, PARPi prevent repair of N7-guanine and N3-adenine methylation induced by TMZ, increase DNA strand breaks and is responsible of a TMZ chemosensitization [ 53 , 54 ] even on glioblastoma stem cell [ 55 ]. Data concerning the role of PARPi as TMZ chemosensitizer depending on MGMT status stay debated [ 40 , 56 58 ]even if some phase II-III clinical trials recruits only patients with methylated MGMT (NCT0215298). Moreover, PARPi could induce synthetic lethality in PTEN deleted glioblastoma (36% of Glioblastoma) suggesting that it might be logical to treat PTEN-deficient glioblastomas with PARP inhibitors in the future [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to inhibition of BER, PARPi prevent repair of N7-guanine and N3-adenine methylation induced by TMZ, increase DNA strand breaks and is responsible of a TMZ chemosensitization [ 53 , 54 ] even on glioblastoma stem cell [ 55 ]. Data concerning the role of PARPi as TMZ chemosensitizer depending on MGMT status stay debated [ 40 , 56 58 ]even if some phase II-III clinical trials recruits only patients with methylated MGMT (NCT0215298). Moreover, PARPi could induce synthetic lethality in PTEN deleted glioblastoma (36% of Glioblastoma) suggesting that it might be logical to treat PTEN-deficient glioblastomas with PARP inhibitors in the future [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, using MGMT non-methylated GBM models, a recent study showed that the association of veliparib, a PARP1 inhibitor, with IR inhibited colony formation, reduced the levels of MRE11 (HR pathway) and increased apoptosis. Furthermore, the oral administration of veliparib plus concomitant RT induced apoptosis and diminished cell proliferation in mice (Jue et al, 2017).…”
Section: Dna Repair and Gbm Resistance To Treatmentmentioning
confidence: 96%
“… 36 These hypermutated tumors may be sensitive to immune checkpoint inhibitors, 22 including programmed death 1 (PD-1) inhibitors 65 and poly-adenosine diphosphate ribose polymerase inhibitors. 66 However, clinical trial data supporting these hypotheses have yet to emerge. Another study used whole-genome and multisector exome sequencing of 23 predominantly IDH -wildtype GBM and matched recurrent tumors.…”
Section: Molecular Profiling Offers New Possibilities For Diagnosis Amentioning
confidence: 99%